Control of Development, Secondary Metabolism and Light-Dependent Carotenoid Biosynthesis by the Velvet Complex of Neurospora crassa. Issue 3 (8th May 2019) - Bayram, Özlem Sarikaya; Dettmann, Anne; Karahoda, Betim; Moloney, Nicola M; Ormsby, Tereza; McGowan, Jamie; Cea-Sánchez, Sara; Miralles-Durán, Alejandro; Brancini, Guilherme T P; Luque, Eva M; Fitzpatrick, David A; Cánovas, David; et al.
Abstract: Neurospora crassa is an established reference organism to investigate carotene biosynthesis and light regulation. However, there is little evidence of its capacity to produce secondary metabolites. Here, we report the role of the fungal-specific regulatory velvet complexes in development and secondary metabolism (SM) in N. crassa . Three velvet proteins VE-1, VE-2, VOS-1, and a putative methyltransferase LAE-1 show light-independent nucleocytoplasmic localization. Two distinct velvet complexes, a heterotrimeric VE-1/VE-2/LAE-1 and a heterodimeric VE-2/VOS-1 are found in vivo . The heterotrimer-complex, which positively regulates sexual development and represses asexual sporulation, suppresses siderophore coprogen production under iron starvation conditions. The VE-1/VE-2 heterodimer controls carotene production. VE-1 regulates the expression of >15% of the whole genome, comprising mainly regulatory and developmental features. We also studied intergenera functions of the velvet complex through complementation of Aspergillus nidulans veA, velB, laeA, vosA mutants with their N. crassa orthologs ve-1, ve-2, lae-1, and vos-1, respectively. Expression of VE-1 and VE-2 in A. nidulans successfully substitutes the developmental and SM functions of VeA and VelB by forming two functional chimeric velvet complexes in vivo, VelB/VE-1/LaeA and VE-2/VeA/LaeA, respectively. Reciprocally, expression of veA restores the phenotypes of the N. crassa ve-1 mutant. All N. crassa velvet proteins heterologously expressed in A. nidulans are localized to the nuclear fraction independent of light. These data highlight the conservation of the complex formation in N. crassa and A. nidulans . However, they also underline the intergenera similarities and differences of velvet roles according to different life styles, niches and ontogenetic processes.